PECULIARITIES OF USING OF THE HIGH-TEST CAST-IRON WASTES AT PRODUCTION BY CASTING IN THE CONSTANT SLUG MODES FOR MATING RINGS OF TURBOCOMPRESSORS - A. M. Bodjako; S. V. Galagajev; A. A. Suponev (Литьë и металлургия)
There are studied the peculiarities of the problem of" using of waste in the form of intrinsic recovery at receiving by casting in the constant ingots modes for the mating rings of turbo-compressors. It is shown, that presence of more than 50 % of the intrinsic recovery in the burden of induction melting allows to decrease the amount of the spheroidizing modifier of type FSMg 7 at production of cast iron with ball-shape graphite up to 1,3—1,4% without impairment of the graphite impurities form.